A TC4-xEr alloy prepared by laser powder bed
By adding trace erbium elements to the powder preparation of LPBF TC4 alloy to optimize its structure, the problems of poor plasticity and anisotropy of LPBF TC4 alloy are solved, and the coordinated optimization of strength and plasticity is achieved, reducing production costs and time.
Patent Information
- Application Number
- CN202411846654.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-04
AI Technical Summary
The LPBF TC4 alloy has poor plasticity during the preparation process, and its strength and hardness will be greatly reduced after heat treatment, resulting in performance anisotropy, limiting its application in service scenarios.
By adding trace amounts of rare earth element erbium (TC4-xEr) to the powder preparation raw materials, the structural structure of titanium alloy samples is optimized without the need to adjust the LPBF process parameters a lot, promoting the isometric transformation of columnar crystals, improving plasticity and maintaining strength.
It realizes optimizing plasticity on the basis of ensuring strength, reduces the annealing heat treatment temperature and time, reduces the electrical cost and time cost of industrial production, and alleviates the anisotropy problem of performance.
Smart Images

Figure CN119747684A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy material preparation, and in particular to a TC4-xEr alloy prepared by a laser powder bed. Background Art
[0002] Laser powder bed fusion (LPBF) technology has the characteristics of high energy utilization, high vacuum degree and no pollution, good density of molded samples, high dimensional accuracy and small roughness. It has unique advantages in preparing small volume, high dimensional accuracy, strong complexity and high added value metal parts.
[0003] Titanium and titanium alloys have excellent mechanical and physicochemical properties such as low density, high specific strength, corrosion resistance, heat resistance, excellent low-temperature performance, weldability, good biocompatibility and non-magnetism. They have important applications in aerospace, military industry, biomedicine and other fields. Among the many commercial titanium alloys, Ti-6Al-4V (TC4) accounts for more than 50% of the usage. It is widely used in LPBF due to its excellent weldability and mechanical and chemical properties. The performance of LPBF TC4 samples mainly depends on the sample's organization, such as the initial β phase morphology, the distribution state of the β phase, the α phase morphology and distribution state, and the proportion of the α phase and β phase in the organization. Due to the large temperature gradient and cooling rate (~10 6K / s), the vast majority of typical structures in LPBF TC4 alloy samples are acicular martensite α' structures distributed in β columnar crystals. Compared with the traditional cast TC4 alloy, LPBF TC4 alloy exhibits extremely high tensile strength (~1200MPa), but due to the complex thermal history in the LPBF preparation process, there are serious lattice distortion and other defects in the martensite α', which makes the α' structure of hexagonal close-packed (HCP) structure show extremely low plasticity and cannot meet industrial requirements. In order to alleviate the problem of poor plasticity of LPBF TC4 samples, the industry often uses a heat treatment system of 800℃-2h to decompose the martensite α' into α+β lath structure. For example, Vrancken et al. obtained fine lath structure using a heat treatment system of 850℃-2h. Although heat treatment can solve the plasticity problem of LPBF TC4 alloy, the growth and coarsening of laths will cause the sample to lose a lot of strength (~200MPa) and hardness. At the same time, the β columnar crystal structure in the sample cannot be improved in the above heat treatment system, resulting in obvious anisotropy in the performance of the LPBF TC4 alloy, which greatly reduces the stability of the sample during service and limits the service scenario. In response to this phenomenon, most researchers choose to optimize the LPBF process to achieve the effect of transforming from columnar crystals to equiaxed crystals, but this in-situ structure control method is often achieved by increasing heat input, which makes it difficult to take into account both structure and performance, and the process parameter development cycle is long.
[0004] At present, most of the organizational optimization of existing LPBF TC4 alloys in the industry starts from the powder back-end, and the organizational optimization of LPBF TC4 alloys is carried out in-situ or ex-situ through the adjustment of LPBF process parameters and the optimization of heat treatment system. The optimization of process parameters often requires a long development cycle. For example, Xu Wei's research group at Monash University achieved the in-situ decomposition of martensite α' through parameter optimization, and was able to directly obtain α+β lath structure through the LPBF process, but the optimization effect of process parameters on the organization is often greatly limited by the premise, and the scientific research value is greater than the industrial value; the 800℃-2h-FC heat treatment system is commonly used in industry to improve the organization of LPBF TC4, but the coarsening and growth of laths will lead to a significant reduction in strength. At the same time, the total time of heating-furnace cooling-removal of the above heat treatment system takes about 8 hours, which is inefficient.
[0005] Therefore, in order to solve the above problems, the present invention provides a TC4-xEr alloy prepared by a laser powder bed. The present invention aims to start from the preparation of LPBF TC4 powder, by adding a trace amount of rare earth element erbium (TC4-xEr) to the raw materials for powder preparation, to modify and optimize the LPBF titanium alloy sample without the need for a large amount of LPBF process parameter redevelopment. Summary of the invention
[0006] The purpose of the present invention is to provide a TC4-xEr alloy prepared by a laser powder bed to fill the gap in the current technology.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A method for preparing TC4-xEr alloy by laser powder bed preparation comprises the following steps:
[0009] (1) Smelting and preparation of raw materials for powder making: When smelting and preparing raw materials, a certain proportion of trace rare earth element Er is added for smelting to obtain TC4-xEr raw materials for powder making, wherein the TC4-xEr raw materials for powder making include Al5.5-6.75wt%, V3.5-4.5wt%, Fe≤0.30wt%, Er≤0.10wt%, C≤0.08wt%, N≤0.05wt%, H≤0.01wt%, O≤0.07wt%, and the balance Ti, in percentage;
[0010] (2) Preparation of powder raw materials: The TC4-xEr powder raw materials obtained by smelting in step (1) are subjected to a powder making process to prepare powder to obtain powder raw materials, wherein the powder raw materials, by percentage, include Al 5.5-6.75wt%, V 3.5-4.5wt%, Fe ≤ 0.30wt%, Er ≤ 0.10wt%, C ≤ 0.08wt%, N ≤ 0.05wt%, H ≤ 0.01wt%, O ≤ 0.07wt%, and the balance Ti;
[0011] (3) LPBF TC4-xEr alloy preparation: LPBF TC4-xEr alloy was prepared by laser powder bed additive manufacturing equipment. The LPBF process parameters were the conventional TC4 printing parameters in the industry, specifically: layer thickness: 30-60 μm; laser spot: 75-100 μm; laser power: 260-280 W; scanning rate: 1200 mm / s; substrate preheating temperature: no preheating; scanning strategy: 67° zigzag;
[0012] (4) After the preparation of the LPBF TC4-xEr alloy in step (3) is completed, the LPBF TC4-xEr alloy material is subjected to annealing heat treatment to eliminate residual stress and decompose the martensite structure in the printed state to present an α+β fine lath structure.
[0013] In the above technical solution, after the preparation of the LPBF TC4-xEr alloy in step (3) is completed, the LPBF TC4-xEr alloy material is subjected to annealing heat treatment to meet the stability of the material under service conditions, thereby eliminating residual stress and decomposing the martensitic structure in the printed state to make it present an α+β fine lath structure, thereby optimizing plasticity while ensuring strength.
[0014] Preferably, in step (1), the obtained TC4-xEr powder making raw material is in the form of, but not limited to, ingots, rods, and wires.
[0015] Preferably, in step (2), the powder making process includes but is not limited to: gas atomization, plasma atomization, and mechanical ball milling powder making process.
[0016] Preferably, in step (2), the obtained powder raw material has a sphericity of more than 90%, a powder hollow ratio of no more than 5%, and a powder particle size specification of 15-53 microns, wherein powder D10: 18-25 microns; D50: 30-40 microns; D90: 53-60 microns.
[0017] Preferably, in step (4), the annealing heat treatment temperature of the LPBF TC4-xEr alloy material is 650-800°C.
[0018] The present application also claims protection for a TC4-xEr alloy prepared by a laser powder bed, which is prepared by the above-mentioned method for preparing the TC4-xEr alloy by a laser powder bed.
[0019] Working mechanism of the present invention:
[0020] The present invention aims to start with the preparation of LPBF TC4 powder, and by adding a trace amount of rare earth element erbium (TC4-xEr) to the raw materials for powder preparation, the LPBF titanium alloy sample is modified and optimized without the need for a large amount of LPBF process parameter redevelopment; since the solid solubility of erbium in titanium alloy is relatively low, a very small amount of erbium can be added to form second phase nanoparticles such as Er2O3 and Al2Er with O and Al elements in TC4; in the LPBF production process, the laser melts the powder to form a molten pool, and the nanoparticles provide nucleation points for grain growth in the molten pool, inhibit the tendency of epitaxial growth of grains in the sample, promote the transformation of columnar crystals to equiaxed, and alleviate the workpiece The anisotropy of performance in service engineering; the increase in nucleation sites can also effectively reduce the initial β grain size, further refine the needle-shaped martensite α', so that the sample can obtain a finer lath structure after annealing, and lose as little strength as possible on the basis of improving plasticity. At the same time, the Er2O3 and Al2Er second phase nanoparticles in the sample can play a role in dispersion strengthening; in addition, Al and O are α-stabilizing elements, and the formation of Er2O3 and Al2Er can form an α-stabilizing element-poor zone, which reduces the driving force required for martensite decomposition and reduces the temperature and time of annealing heat treatment, thereby reducing the electrical cost and time cost of industrial production.
[0021] Due to the application of the above technical solution, the present invention has the following beneficial effects compared with the prior art:
[0022] 1. The present invention adds a trace amount of rare earth element erbium (TC4-xEr) to the raw materials for powder preparation, thereby modifying and optimizing the LPBF titanium alloy sample without the need for a large amount of LPBF process parameter redevelopment;
[0023] 2. The present invention adds a trace amount of rare earth element erbium. Since the solid solubility of erbium in titanium alloy is low, a very small amount of erbium can form second phase nanoparticles such as Er2O3 and Al2Er with O and Al elements in TC4. In the LPBF production process, the laser melts the powder to form a molten pool. The nanoparticles provide nucleation points for grain growth in the molten pool, inhibit the tendency of epitaxial growth of grains in the sample, promote the transformation of columnar crystals to equiaxed, and alleviate the anisotropy of the performance of the workpiece in service engineering.
[0024] 3. The increase of nucleation sites in the present invention can also effectively reduce the initial β grain size, further refine the needle-shaped Martensitic α', so that the sample can obtain a finer lath structure after annealing, and lose as little strength as possible on the basis of improving plasticity. At the same time, the Er2O3 and Al2Er second phase nanoparticles in the sample can play a role of dispersion strengthening;
[0025] 4. In the present invention, Al and O are α-stabilizing elements. The formation of Er2O3 and Al2Er can form an α-stabilizing element-poor zone, reduce the driving force required for martensite decomposition, reduce the temperature and time of annealing heat treatment, and thus reduce the electrical cost and time cost of industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, some of the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be made based on these drawings without paying any creative work.
[0027] Figure 1 It is a comparison diagram of the printed tissue of TC4-0.1Er of Example 1 of the present invention and TC4 of Comparative Example 1;
[0028] Figure 2 Comparison diagram of heat-treated structures of TC4-0.1Er of Example 1 of the present invention and TC4 of Comparative Example 1;
[0029] in, Figure 1 The left picture in the middle is Example 1, and the right picture is Comparative Example 1; Figure 2 The left picture in the middle is Example 1, and the right picture is Comparative Example 1. DETAILED DESCRIPTION
[0030] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, a specific implementation scheme is now described in detail.
[0031] The present invention is further described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to the different requirements of specific use, and the implementation conditions not indicated are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0032] Example 1
[0033] See attached Figure 1 And attached Figure 2 This embodiment provides a method for preparing TC4-xEr alloy by laser powder bed preparation, comprising the following steps:
[0034] (1) Smelting and preparing the raw materials for powder making: adding a certain proportion of trace rare earth element Er element to the raw materials for smelting and preparing the raw materials; obtaining the TC4-xEr raw materials for powder making, the forms of the obtained TC4-xEr raw materials for powder making include but are not limited to: ingots, rods, wires;
[0035] (2) Preparation of powder raw materials: The TC4-xEr powder raw materials obtained by smelting in step (1) are subjected to a powder making process to obtain powder raw materials; the powder making process includes but is not limited to: gas atomization, plasma atomization, mechanical ball milling process; the obtained powder raw materials have a sphericity of more than 90%, a powder hollow rate of no more than 5%, and a powder particle size specification of 15-53 microns, wherein the powder D10 is 18-25 microns; D50 is 30-40 microns; and D90 is 53-60 microns;
[0036] (3) Preparation of LPBF TC4-xEr alloy: Preparation of LPBF TC4-xEr alloy by laser powder bed additive manufacturing equipment;
[0037] Specifically, this embodiment is the preparation of LPBF TC4-0.1Er alloy, which is prepared according to the above method, wherein the elemental composition of the powder raw material is specifically shown in Table 1.
[0038] Table 1
[0039] element Ti Al V Fe Er C N H O Content.wt% margin 6.25 4.05 0.16 0.10 0.008 0.006 0.004 0.08
[0040] The LPBF printing process parameters are shown in Table 2.
[0041] Table 2
[0042] Layer thickness Laser spot Laser power Scan rate Substrate preheating temperature Scanning strategy 30 microns 80 microns 280W 1200mm / s No preheating 67° zigzag
[0043] Comparative Example 1
[0044] This comparative example is a conventional TC4, and the LPBF equipment and process parameters are exactly the same as those in Example 1.
[0045] By the attached Figure 1 It can be seen that after adding 0.1wt%, the epitaxial growth trend in TC4-0.1Er is suppressed, showing an obvious transformation from columnar crystals to equiaxed crystals, and the initial β grains show a nearly equiaxed crystal morphology. At the same time, the needle-shaped martensite α' is finer than that of the conventional printing table LPBF TC4 alloy; the nearly equiaxed crystal structure and the finer martensitic structure provide the material with more stable performance (isotropic) and higher strength; at the same time, the presence of Er2O3 and Al2Er nanosecond phase particles in Example 1 can increase the material strength and work hardening ability. The mechanical properties of Example 1 and Comparative Example 1 are shown in Table 3.
[0046] Table 3
[0047]
[0048] After the LPBF process, Example 1 and Comparative Example 1 were subjected to annealing heat treatment; the heat treatment temperature was selected to be 700°C-2h-FC, and the Example 1 and Comparative Example 1 were subjected to heat treatment annealing respectively; after the heat treatment, the organization of Example 1 and Comparative Example 1 was characterized by scanning electron microscopy, as shown in FIG. Figure 2 Shown are the backscattered diffraction patterns of Example 1 (left) and Comparative Example 1 (right). It can be seen that the martensite α' in TC4-0.1Er can be completely decomposed under the heat treatment of 700 degrees Celsius, while the comparative example 1 can only be partially decomposed. This is because Al and O are α-stabilizing elements. The formation of Er2O3 and Al2Er in Example 1 can form an α-stabilizing element-poor zone, which reduces the driving force required for martensite decomposition and reduces the temperature and time of annealing heat treatment. Conventional TC4 material can achieve complete decomposition of martensite only by annealing heat treatment at 800℃-2h-FC.
[0049] In summary, the present invention starts with the preparation of LPBF TC4 powder, and by adding a trace amount of rare earth element erbium (TC4-xEr) to the raw materials for powder preparation, the LPBF titanium alloy sample is modified and optimized without the need for a large amount of LPBF process parameter redevelopment; since the solid solubility of erbium in titanium alloy is relatively low, the addition of a very small amount of erbium can form second phase nanoparticles such as Er2O3 and Al2Er with O and Al elements in TC4; in the LPBF production process, the laser melts the powder to form a molten pool, and the nanoparticles provide nucleation points for grain growth in the molten pool, inhibit the tendency of epitaxial growth of grains in the sample, promote the transformation of columnar crystals to equiaxed, and alleviate the workpiece The anisotropy of performance in service engineering; the increase in nucleation sites can also effectively reduce the initial β grain size, further refine the needle-shaped martensite α', so that the sample can obtain a finer lath structure after annealing, and lose as little strength as possible on the basis of improving plasticity. At the same time, the Er2O3 and Al2Er second phase nanoparticles in the sample can play a role in dispersion strengthening; in addition, Al and O are α-stabilizing elements, and the formation of Er2O3 and Al2Er can form an α-stabilizing element-poor zone, which reduces the driving force required for martensite decomposition and reduces the temperature and time of annealing heat treatment, thereby reducing the electrical cost and time cost of industrial production.
[0050] The above-mentioned embodiments only express the preferred implementation of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A method for preparing TC4-xEr alloy by laser powder bed preparation, characterized in that: The steps include: (1) Smelting and preparation of raw materials for powder making: When smelting and preparing raw materials, a certain proportion of trace rare earth element Er is added for smelting to obtain TC4-xEr raw materials for powder making, wherein the TC4-xEr raw materials for powder making include Al5.5-6.75wt%, V3.5-4.5wt%, Fe≤0.30wt%, Er≤0.10wt%, C≤0.08wt%, N≤0.05wt%, H≤0.01wt%, O≤0.07wt%, and the balance Ti, in percentage; (2) Preparation of powder raw materials: The TC4-xEr powder raw materials obtained by smelting in step (1) are subjected to a powder making process to prepare powder to obtain powder raw materials, wherein the powder raw materials, by percentage, include Al 5.5-6.75wt%, V 3.5-4.5wt%, Fe ≤ 0.30wt%, Er ≤ 0.10wt%, C ≤ 0.08wt%, N ≤ 0.05wt%, H ≤ 0.01wt%, O ≤ 0.07wt%, and the balance Ti; (3) Preparation of LPBF TC4-xEr alloy: Preparation of LPBF TC4-xEr alloy by laser powder bed additive manufacturing equipment; (4) After the preparation of the LPBF TC4-xEr alloy in step (3) is completed, the LPBF TC4-xEr alloy material is subjected to annealing heat treatment to eliminate residual stress and decompose the martensite structure in the printed state to present an α+β fine lath structure.
2. The TC4-xEr alloy prepared by laser powder bed according to claim 1, characterized in that: In step (1), the obtained TC4-xEr powder making raw material may be in the form of, but not limited to, ingots, rods, and wires.
3. The method for preparing TC4-xEr alloy by laser powder bed preparation as claimed in claim 1, characterized in that: In step (2), the powder making process includes but is not limited to: gas atomization, plasma atomization, and mechanical ball milling powder making process.
4. The method for preparing TC4-xEr alloy by laser powder bed preparation as claimed in claim 1, characterized in that: In step (2), the obtained powder raw material has a sphericity of more than 90%, a powder hollow rate of no more than 5%, and a powder particle size specification of 15-53 microns, wherein powder D10: 18-25 microns; D50: 30-40 microns; D90: 53-60 microns.
5. The method for preparing TC4-xEr alloy by laser powder bed preparation as claimed in claim 1, characterized in that: In step (4), the annealing heat treatment temperature of the LPBF TC4-xEr alloy material is 650-800°C.
6. A TC4-xEr alloy prepared by laser powder bed, characterized in that: The TC4-xEr alloy is prepared by the preparation method of the laser powder bed according to any one of claims 1 to 5.